Impacts of the joint adoption of improved varieties and chemical fertilizers on rice productivity in Bolivia: implications for Global Food Systems - Martinez, Jose Maria; Labarta, Ricardo A.; Gonzalez, Carolina (Frontiers in Sustainable Food Systems, 2023)
Rice research and technology development in Latin America has increased yields and offered the opportunity for several countries to contribute to global food security by becoming net exporters of this cereal. In spite of the broad availability of rice technologies in the region, rice yields remain substantially low in countries like Bolivia. This study examines how Bolivian rice growers make simultaneous decisions about adopting improved varieties and chemical fertilizers and how this joint decision influences the productivity of this crop. By exploiting a nationally representative survey of rice producers, we use a multinomial logit model and an optimal instrumental variable approach to study both the correlates of technology adoption and the impacts of this adoption on rice yields. Our findings suggest that partial adoption of rice varieties or fertilizers does not affect yields, but the joint adoption of these technologies can almost double rice productivity. Promoting packages of agricultural technologies—instead of single technologies within efforts to make these technologies available for small farmers—would exploit the complementarities of different technologies and boost rice yields in Bolivia. The implications would not only be to achieve the desired self-sufficiency in rice production but also to follow similar pathways of other countries in the region that have become net exporters of rice and are contributing to Global Food Systems.